Study of Self-Reported Morbidity Profile among the Rural Tribal Population in a District of Western India - Jay R. Patwa; Rakesh M. Patel; Shashwat S. Nagar; Niraj B. Pandit (Indian Association of Preventive and Social Medicine, 2020)
Introduction: India has a dual burden of both communicable as well as non-communicable disease. The morbidity pattern of a population is considered as a proxy measure to understand the country's health status. Objectives: To study the demographic profile of villages & compare it with national level. To assess the common morbidity pattern, its age-wise distribution and proportion of multi-morbidity in the community. Methods: The present cross-sectional study was a part of routine Rural Health Training Centre (RHTC) work. For present study, 5 out of 15 villages under the Primary Health Centre (PHC) Bahadarpur were included with purposive sampling. House to house visit were done. Data were collected by trained intern doctors posted at RHTC from November 2014 to January 2015. All villagers who were living in those villages for more than a year and fitting in the definition of a family were included in the study. Results: Oro-dental diseases, ophthalmic diseases, musculoskeletal diseases & non-communicable diseases were top in prevalence list. Prevalence of multi-morbidity for non-communicable diseases was 14.68%. In children below the age of five years most common morbidity was acute respiratory infection. Among children aged between 5 years to 14 years the most common morbidity was ophthalmic disease while among 15-60 years of age group & in geriatric population oro-dental disease was most common morbidity. Conclusion: The present study gave prevalence rates for various diseases. Acute respiratory infections are still major problem among children. Multimorbidity is a new phenomenon which was observed in rural tribal villages. Such community-based prevalence of different diseases will help to understand the changing disease pattern in the community